THE EPISTEMOLOGY OF ISLAMIC PHILOSOPHY: A Chronological Review - Amril Amril; Ahmad Khoirul Fata; Mohd Roslan Mohd Nor (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This article describes the various forms of Islamic philosophy because some scholars claim that philosophical thought in Islam has declined after Ghazâlî's criticism. This library research uses qualitative method and historical approach, and focuses on examining the distinctive characteristics of each school of Islamic philosophical thought by emphasizing its epistemological aspects. This article shows that philosophy in Islamic world is very dynamic and not in a single character. In each period, the Islamic philosophy reveals a variety of patterns. To facilitate the discussion, this article is elaborated on a series of times and examines the distinctive patterns of epistemology that developed in each epoch. Although ontologically they are similar, there are epistemic differences in the philosophy developed by Muslim philosophers: Peripateticism, which dominated during the classical Islamic period (850-1250); 'Irfânâyah and two schools of wisdom (al-hikmah al-ishraqîyah/illumination theosophy and al-hikmah al-muta'âlîyah/transcendent theosophy), which dominated in the medieval Islamic period (1250-1850); and the school of al-hikmat al-ladunîyah/perennialist theosophy and al-'aqalîyah in the contemporary Islamic period (1850-present). This diversity emerged as a response to different challenges and adaptations to local situations.